The knowledge gap in world politics: Assessing the sources of citizen awareness of the United Nations Security Council. Issue 4 (11th January 2016) - Dellmuth, Lisa Maria
Abstract: The past decades have seen a significant expansion in the scope and authority of international organisations (IOs), raising questions about who participates and is represented in the public contestation of IOs. An important precondition for citizens to become critically involved in the public debate about an IO is that they are aware of the politics of that IO. This article sheds light on this largely unexplored issue, asking why some citizens are more aware of IOs than others. This question is examined in the context of a powerful international organisation, the United Nations Security Council. Using a multilevel analysis of citizens in 17 Asian and European countries, this article argues that citizen knowledge about the Council is shaped by economic conditions and cosmopolitan identity. Higher levels of knowledge are found among the wealthier, and there is some evidence that income inequality depresses knowledge among poorer citizens. Furthermore, citizens identifying with groups or individuals across nation-state borders are more likely to know more about the Council. The article sketches broader implications for the study of the politicisation of IOs and citizen representation in the public contestation of IOs.